Religiosity and Neuroticism: Exploring the Psychological Characteristics of Coastal Communities in Tlocor - Titi Nur Utami; Mamang Efendy; Rahma Kusumandari; Supriyanto Supriyanto; Ivan Ramandhika A. Jatnika (Psikologi Prima, 2026)
This study aimed to examine the relationship between religiosity and tendencies toward neuroticism among coastal communities in Tlocor Beach. Using a quantitative correlational design with 110 respondents, data were collected through religiosity and neuroticism scales. Simple linear regression analysis indicated no significant relationship between the two variables. These findings suggest that levels of religiosity, whether high or low, do not influence tendencies toward neuroticism among coastal populations. The discrepancy between these results and previous studies may be attributed to the socio-cultural characteristics of the community and the potential presence of social desirability bias in completing the instruments.